PENGARUH LIKUIDITAS, PROFITABILITAS, DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL PERUSAHAAN - Erni Kurniasari; Listiawati (JURNAL CAFETARIA, 2021)
This research aims to determine the influence of liquidity, profitability, and asset structure on capital structure partially and simultaneously. The population in this research are pharmaceuticals companies listed on the Indonesian Stock Exchange in the period 2015-2019. The sample selection used purposive sampling method. The sample in this research are 7 pharmaceuticals companies listed on the Indonesian Stock Exchange for 5 years in the period 2015-2019. Based on the results of this research, the researcher concludes that partially profitability and asset structure have a significant influence on the capital structure, while liquidity has no significant influence on the capital structure. Simultaneously, liquidity, profitability, and asset structure have a significant influence on the capital structure. The coefficient of determination is 0,517, showed that liquidity, profitability, and asset structure have 51,7% to the capital structure, while 48,3% are determined by another variables.